PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA DENGAN DIMEDIASI KEPUASAN KERJA PADA KARYAWAN WAROENG SPESIAL SAMBAL YOGYAKARTA - Inayat Hanum Indriati (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
The research aims to find out: 1) the influence of leadership on job satisfaction; the influence of leadership on performance; 3) the effect of compensation on job satisfaction; 4) the effect of compensation on performance; 5) the effect of job satisfaction on performance; 6) indirect effect of leadership on employee performance mediated by job satisfaction; and 7) indirect effect of compensation on the performance of employees of Waroeng SS Yogyakarta, mediated by job satisfaction. The study was conducted on employees of Waroeng SS Yogyakarta, with a population of 500 employees. The sample in this study was set at 200 using accidental sampling. Data collection is done using a questionnaire. Data analysis techniques are used Structural Equation Model (SEM). The results showed that leadership had a positive and significant effect on job satisfaction, with a CR of 3.942 and p of 0.000 (p <0.05). Leadership has a positive and significant effect on performance, with CR of 2.327 and p of 0.020 (p <0.05). Compensation has a positive and significant effect on job satisfaction, with CR of 2.432 and p of 0.015 (p <0.05). Compensation has a positive and significant effect on performance, with CR of 2.876 and p of 0.004 (p <0.05). Job satisfaction has a positive and significant effect on performance, with CR of 3.800 and p of 0.000 (p <0.05). Leadership has an indirect effect on the performance of employees of Waroeng SS Yogyakarta, mediated by job satisfaction, with Sobel's Z of 2.732911 and p of 0.006277732 (p <0.05). Compensation has an indirect effect on the performance of employees of Waroeng SS Yogyakarta, mediated by job satisfaction, with Sobel's Z of 2.040175 and p of 0.041332877 (p <0.05).